Tracking Progress of National Health Summit Declarations - Health Policy Analysis: A Qualitative Study - Ashis Shrestha; Lisasha Poudel; Dipesh Tikhatri; Sushant Regmi; Jay Bhushan Jha; Shreya Baniya; Mandish Prasad Phuyal; Akanshya Prasai; Sunil Kunwar; Amit Chand; Prakriti Karki; Nurusha Tamrakar; et al. (Journal of Nepal Medical Association)
Introduction: The National Health Summit is a policy discussion platform that advocates the policy statement stated by National Health Policy 2019 which results in a set of declarations to address issues in the health system. This study’s objective is to monitor the extent of declaration’s implementation, its facilitators-barriers, and to formulate recommendation for future National Health Summit declarations and implementation strategies. Methods: This is a qualitative study conducted by Nepal Medical Association. in November-December 2024. Ethical approval from Nepal Health Research Council, Ethical Review Board (Reference number: 1069). The study was designed using the Realistic Evaluation Framework to look into the “context” which are the external factors impacting implementation of the declarations, the “mechanism” which are key elements facilitating or hindering policy changes, and the “outcome” which were the tangible results of NHS declarations. Results: Review and analysis of the participant responses identified policy influene and advocacy as contexts. The mechanisms identified were political and bureaucratic challenges, collaboration, finaicial hurdles, commitment, accountability, leadership, evidence based practices. The outcome discussed were health system strengthening, health workforce, governance, innovation, advocacy and digaital transformations. Conclusions: Implementation of declaration is challenging, with fragmentation as major health issues, however, continuous advocacy has had a synergistic effect in implementation and prioritization of the policy.